(untitled) (Studia theodisca, 2011)
This paper focuses on para-religious elements in the poetry of Stefan George, with reference to the cycle Waller im Schnee, which occupies the middle of the first section in the collection Das Jahr der Seele (1897). The waning of the sentimental relationship between the protagonist and his interlocutor is linked to the loss of effectiveness of a priestly ritual, which in the past had held the two together and whose significance has now diminished through perplexity and misunderstanding.